Aleutian Disease: An Emerging Disease in Free-Ranging Striped Skunks (Mephitis mephitis) From California. (November 2015) - LaDouceur, E. E. B.; Anderson, M.; Ritchie, B. W.; Ciembor, P.; Rimoldi, G.; Piazza, M.; Pesti, D.; Clifford, D. L.; Giannitti, F.
Aleutian disease virus (ADV, Amdovirus, Parvoviridae ) primarily infects farmed mustelids (mink and ferrets) but also other fur-bearing animals and humans. Three Aleutian disease (AD) cases have been described in captive striped skunks; however, little is known about the relevance of AD in free-ranging carnivores. This work describes the pathological findings and temporospatial distribution in 7 cases of AD in free-ranging striped skunks. All cases showed neurologic disease and were found in a 46-month period (2010–2013) within a localized geographical region in California. Lesions included multisystemic plasmacytic and lymphocytic inflammation (ie, interstitial nephritis, myocarditis, hepatitis, meningoencephalitis, pneumonia, and splenitis), glomerulonephritis, arteritis with or without fibrinoid necrosis in several organs (ie, kidney, heart, brain, and spleen), splenomegaly, ascites/hydrothorax, and/or encephalomalacia with cerebral microangiopathy. ADV infection was confirmed in all cases by specific polymerase chain reaction and/or in situ hybridization. The results suggest that AD is an emerging disease in free-ranging striped skunks in California.